Cachectic body composition and inflammatory markers portend a poor prognosis in patients with locally advanced pancreatic cancer treated with chemoradiation - Naumann, Patrick; Eberlein, Jonathan; Farnia, Benjamin; Liermann, Jakob; Hackert, Thilo; Debus, Jürgen; Combs, Stephanie E. (Cancers, 2019)
Background: Patients with pancreatic cancer often develop cancer cachexia, a complex multifactorial syndrome with weight loss, muscle wasting and adipose tissue depletion with systemic inflammation causing physical impairment. In patients with locally advanced pancreatic cancer (LAPC) neoadjuvant treatment is routinely performed to allow a subsequent resection. Herein, we assess body composition and laboratory markers for cancer cachexia both before and after neoadjuvant chemoradiation (CRT). Methods: Subcutaneous fat (SCF), visceral fat (VF), skeletal muscle (SM), weight and laboratory parameters were determined longitudinally in 141 LAPC patients treated with neoadjuvant CRT. Changes during CRT were statistically analyzed and correlated with outcome and Kaplan–Meier curves were plotted. Different prognostic factors linked to cachexia were assessed by uni- and multivariable cox proportional hazards models. Results: There was a significant decrease in weight as well as SCF, VF and SM during CRT. The laboratory parameter C-reactive protein (CRP) increased significantly, whereas there was a significant decrease in leukocyte count, hemoglobin, albumin and cholinesterase as well as in the tumor marker CA 19.9. Cachectic weight loss, sarcopenia, reductions in body compartments SCF, VF and SM, and changes in laboratory markers as well as resection affected survival in univariable analysis. In multivariable analysis, weight loss >5% (HR 2.8), reduction in SM >5% (HR 5.5), an increase in CRP (HR 2.2) or CA 19.9 (HR 1.9), and resection (HR 0.4) remained independently associated with survival, whereas classical cachexia and sarcopenia did not. Interestingly, the subgroup of patients with cachectic weight loss >5% or SM reduction >5% during CRT did not benefit from resection (median survival 12 vs. 27 months). Conclusions: Persistent weight loss and muscle depletion during CRT as well as systemic inflammation after CRT impacted survival more than cachexia or sarcopenia according classical definitions.
Gesehen am 23.12.2019